Genome-wide association study confirms BST1 and suggests a locus on 12q24 as the risk loci for Parkinson's disease in the European population - Saad, M.; Lesage, S.; Saint-Pierre, A.; Corvol, J.-C.; Zelenika, D.; Lambert, J.-C.; Vidailhet, M.; Mellick, G. D.; Lohmann, E.; Durif, F.; Pollak, P.; Damier, P.; et al. (Human molecular genetics, 2011)
We performed a three-stage genome-wide association study (GWAS) to identify common Parkinson's disease (PD) risk variants in the European population. The initial genome-wide scan was conducted in a French sample of 1039 cases and 1984 controls, using almost 500 000 single nucleotide polymorphisms (SNPs). Two SNPs at SNCA were found to be associated with PD at the genome-wide significance level (P < 3 × 10(-8)). An additional set of promising and new association signals was identified and submitted for immediate replication in two independent case-control studies of subjects of European descent. We first carried out an in silico replication study using GWAS data from the WTCCC2 PD study sample (1705 cases, 5200 WTCCC controls). Nominally replicated SNPs were further genotyped in a third sample of 1527 cases and 1864 controls from France and Australia. We found converging evidence of association with PD on 12q24 (rs4964469, combined P = 2.4 × 10(-7)) and confirmed the association on 4p15/BST1 (rs4698412, combined P = 1.8 × 10(-6)), previously reported in Japanese data. The 12q24 locus includes RFX4, an isoform of which, named RFX4_v3, encodes brain-specific transcription factors that regulate many genes involved in brain morphogenesis and intracellular calcium homeostasis.